Multiple Haar basis and $m$-term approximations of functions from the Besov classes. II - Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish the exact-order estimates for the best $m$-term approximations in the multiple Haar basis $H^d$ of functions fromthe Besov classes in the Lebesgue spaces $L_q(I^d)$. We also present a practical algorithm of the construction of the extreme nonlinear m-term aggregates (in a sense of the exact-order estimates for approximations).